Influence of NaCl on the Structure and Dynamics of Phospholipid Layers - Jaksch, Sebastian; Holderer, Olaf; Frielinghaus, Henrich; Koutsioubas, Alexandros; Zolnierczuk, Piotr; Hayward, Dominic William; Förster, Stephan; Müller-Buschbaum, Peter (Frontiers in Physics, 2021)
We present a structural and dynamical analysis of the influence of NaCl on multilayer stacks of phospholipids on a solid surface. To this end, multilayer stacks of phospholipids (L-α-phosphatidylcholine, abbreviated as SoyPC) are investigated with neutron reflectometry, grazing-incidence small-angle neutron scattering (GISANS) and grazing-incidence neutron-spin echo spectroscopy (GINSES). We show both that the NaCl influence on the structure is predominantly on water-headgroup interface and also, that the change in dynamics is restricted to an associated change in the inter-plane viscosity. Using this knowledge, it is possible to model the dynamical behavior of a phospholipid membrane in response to a salt concentration of the solvent using only a single parameter, namely the in-plane viscosity. The excellent agreement with our previously published model also strongly supports the existence of a thermally excited surface mode in phospholipid membranes for close-to-physiological conditions.